Spongy porous body, polishing pad, liquid absorbing pad, cleaning sponge, cultivation sponge, and method for producing spongy porous body
By using ALD technology to form an aqueous film on the inner wall of the sponge-like foam, the problem of elasticity and flexibility decrease when the water property of the foam is improved in the prior art is solved, and the internal water property is improved and the effect of long-term maintenance is achieved.
Patent Information
- Application Number
- JP2023168638
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
The prior art is difficult to maintain its elasticity and flexibility when improving the water-based properties of sponge-like foams, resulting in reduced shape tracking, processability and durability. At the same time, the method of improving surface water properties is limited in effect and is difficult to maintain for a long time.
The aqueous film is formed by using atomic layer deposition (ALD) on the inner wall of the sponge-like foam to ensure that the film layer extends from the surface to the interior of the film to maintain the elasticity and flexibility of the foam.
The internal water-based properties of the foam are improved, the original elasticity and flexibility are maintained, and the maintenance time of water-based properties is extended.
Smart Images

Figure 2025058602000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a sponge-like porous body, a polishing pad, a liquid absorbing pad, a cleaning sponge, a cultivation sponge, and a method for producing a sponge-like porous body. [Background technology]
[0002] Spongy porous bodies are used in a variety of situations. For example, many polishing pads for polishing silicon wafers and glass to a flat surface are made of urethane sponge-like porous bodies. In addition, in inkjet printers, sponge-like porous bodies called waste ink absorbing pads are used to hold waste ink. In addition, various sponge-like porous bodies are commercially available for cleaning purposes such as washing dishes, washing cars, and washing the human body. Furthermore, sponge-like porous bodies are sometimes used instead of soil for hydroponic cultivation.
[0003] For these sponge-like porous bodies, hydrophilicity is often important. For example, in the case of polishing pads, increasing hydrophilicity increases the retention of polishing fluid, and more abrasive grains act on the workpiece surface, improving the polishing properties. Improving the polishing properties not only improves the productivity of the polishing process, but also reduces the amount of rare metals used, which are the raw materials for abrasives. In waste ink absorbing pads, increasing hydrophilicity increases the ink retention, preventing contamination of printer heads due to splashing or leakage from the absorbing pad. In cleaning sponges, increasing hydrophilicity improves the foaming and cleaning effects and increases water absorption. Increasing the hydrophilicity of hydroponic sponges increases their retention of water and fertilizer, allowing them to be supplied to plants more efficiently.
[0004] As a method for increasing the hydrophilicity of a sponge-like porous body, a method of mixing a hydrophilic material into the material of the sponge-like porous body to produce a porous body is known. For example, in Patent Document 1, hydrophilicity is improved by mixing a hydrophilic resin (epoxy resin) into a urethane polishing pad. In addition, a method of spraying a hydrophilic material onto the surface of a sponge-like porous body is known. For example, in Non-Patent Document 1, the polishing properties of a polishing pad are improved by applying a hydrophilic resin, epoxy resin, to the surface of a urethane polishing pad. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-120220 A [Non-patent literature]
[0006] [Non-Patent Document 1] Yohei Kitai, "Improvement of Glass Polishing Characteristics by Using Suede Pads Coated with Epoxy Resin", Transactions of the Japan Society of Mechanical Engineers (Series C), Vol. 79, No. 808 (2013-12), pp. 5019-5028. Summary of the Invention [Problem to be solved by the invention]
[0007] However, the method of Patent Document 1 has a problem in that the hydrophilic material is harder than the original sponge-like porous material, and therefore the sponge-like porous material produced by mixing the hydrophilic material loses elasticity and flexibility. Loss of elasticity and flexibility leads to a decrease in the shape conformability, processability, and durability of the sponge-like porous material.
[0008] In addition, the method of Non-Patent Document 1 can maintain the elasticity and flexibility of the original material of the sponge-like porous body, but only the surface vicinity of the sponge-like porous body can be hydrophilized. In the case of a polishing pad, the surface is scraped off depending on the polishing time, so a polishing pad that has only been hydrophilized near the surface can only maintain hydrophilicity for a short period of time. In addition, there is a problem that the effect of hydrophilization is limited to only the surface vicinity in other sponge-like porous bodies. The problem that the present invention aims to solve is to provide a sponge-like porous body that is stretchable and flexible and has hydrophilic properties from the surface to the inside. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides A sponge-like porous body having a substrate with pores, In the thickness direction from the front surface to the back surface, in the region from a depth of 0% to a depth of 20% or more of the thickness of the sponge-like porous body, the inner walls of the pores are made of a sponge-like porous body having a hydrophilic membrane. The present invention also relates to a polishing pad, a liquid absorbing pad, a cleaning sponge, and a cultivation sponge, each of which has the above-mentioned sponge-like porous body. The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: A preparation step of preparing a substrate having holes; a film formation process of forming a hydrophilic film on the inner wall of the pores by ALD (atomic layer deposition); Including, The method for producing a sponge-like porous body is characterized in that the substrate contains at least one material selected from the group consisting of polyurethane, polyether, and polyethylene. Effect of the Invention
[0010] The hydrophilicity can be improved even to the inside of the sponge-like porous body without impairing the stretchability and flexibility of the porous body. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1(a) is a perspective view of a sponge-like porous body according to an embodiment of the present invention, and FIG. 1(b) is a schematic diagram of a cross section taken along line AA' in FIG. 1(a). [Diagram 2]Fig. 2(a) is a perspective view of a sponge-like porous body (closed-cell type) according to an embodiment of the present invention, Fig. 1(b) is a schematic diagram of a cross section taken along line A-A' in Fig. 2(a), Fig. 2(c) is a schematic diagram showing a state in the middle of drilling vertical holes in the sponge-like porous body with a needle, and Fig. 2(d) is a schematic diagram of a cross section taken along line A-A' in Fig. 2(c) after drilling vertical holes in the sponge-like porous body with a needle. [Diagram 3] FIG. 3(a) is a schematic perspective view showing the CMP polishing process, and FIG. 3(b) is a side view of FIG. 3(a). [Figure 4] FIG. 4 is a schematic perspective view of an inkjet printer. [Diagram 5] FIG. 5 is a schematic diagram of an ALD film formation apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, a mode for carrying out the present invention will be described with reference to the drawings. However, the mode described below is one embodiment of the invention, and the present invention is not limited to this. Furthermore, common configurations will be described with mutual reference to multiple drawings, and descriptions of configurations with common reference numerals will be omitted as appropriate.
[0013] <First embodiment> The first embodiment relates to a sponge-like porous body. The sponge-like porous body of the present invention is a sponge-like porous body having a substrate having pores, The inner walls of the pores have a hydrophilic membrane in a region from a depth of 0% to a depth of 20% or more of the thickness of the sponge-like porous body in the thickness direction from the front surface to the back surface. In this specification, the sponge-like porous body refers to a porous body that contains many pores like a sponge and has flexibility and stretchability.
[0014] FIG. 1(a) shows a perspective view of a sponge-like porous body according to this embodiment. FIG. 1(b) shows a schematic diagram of a cross section along line A-A' in FIG. 1(a). The sponge-like porous body 101 of this embodiment has a base material with many pores 102 therein. In addition, in a region from a surface portion 103 of the sponge-like porous body 101 to a back portion in the thickness direction, from a depth of 0% to a depth of 20% or more of the thickness of the sponge-like porous body 101, the inner walls of the pores have a hydrophilic film (not shown). In a region from a surface portion 103 of the sponge-like porous body 101 to a back portion in the thickness direction, from a depth of 0% to a depth of 50% or more of the thickness of the sponge-like porous body 101, the inner walls of the pores preferably have a hydrophilic film.
[0015] Here, as shown in Fig. 1(b), the thickness direction from the surface to the back surface of the sponge-like porous body refers to the direction perpendicular to the surface and back surfaces of the sponge-like porous body, and 0% in the thickness direction represents the surface of the sponge-like porous body, and 100% represents the back surface of the sponge-like porous body. Therefore, for example, 50% in the thickness direction represents the center in the thickness direction. In this case, in the present invention, the surface of the sponge-like porous body is, for example, the upper surface (upper surface) of the sponge-like porous body in Fig. 1(a) or 1(b), and the back surface of the sponge-like porous body is the bottom surface (bottom surface) of the sponge-like porous body in Fig. 1(a) or 1(b).
[0016] Here, "the inner walls of the pores have a hydrophilic film" does not necessarily mean that the inner walls of all the pores have a hydrophilic film, but rather that 50% or more of the pores have a hydrophilic film. 50% of the pores means 50% or more of the number of pores present in a cross section when the cross section is taken along a plane parallel to the surface portion 103. Therefore, "in the thickness direction from the surface portion toward the back portion, the inner walls of the pores have a hydrophilic film in a region from a depth of 0% to a depth of 20% or more of the thickness of the sponge-like porous body" can be interpreted as follows. It means that 50% or more of the pores also have a hydrophilic film in the surface portion 103 of the sponge-like porous body, and that when the cross section is taken along a plane parallel to the surface portion 103 at a depth of 20% in the thickness direction from the surface portion 103 of the sponge-like porous body, 50% or more of the pores appearing in the cross section have a hydrophilic film.
[0017] A sponge-like porous body generally has elasticity and flexibility. In the present invention, when a sponge-like porous body has elasticity and flexibility, it means that the hardness of the sponge-like porous body is low. As an index showing that the hardness of the sponge-like porous body is low, the sponge-like porous body of the present invention has a hardness of 90 points or less, more preferably 80 points or less, and particularly preferably 75 points or less, as evaluated by a type A durometer (Japanese Industrial Standards, JISK7215). The sponge-like porous body of the present invention preferably has a thickness of 0.1 mm or more. Furthermore, particularly for use as a polishing pad, the thickness of the sponge-like porous body is preferably 0.5 mm or more. This is because if the polishing pad is thinner than 0.5 mm, there is a problem that, for example, the strength is insufficient and the pad is easily broken when fixed to a polishing tool.
[0018] Examples of the material of the substrate of the sponge-like porous body include polyurethane, polyether, polyethylene, and resin materials containing them. The substrate of the sponge-like porous body of the present invention preferably contains at least one selected from the group consisting of polyurethane, polyether, and polyethylene, and more preferably contains polyurethane having excellent flexibility. The substrate of the sponge-like porous body of the present invention preferably contains a foam resin. In this way, the sponge-like porous body can have elasticity and flexibility. In the present invention, the elasticity and flexibility of the sponge-like porous body are represented by the hardness of the sponge-like porous body, and the sponge-like porous body having elasticity and flexibility means, for example, that the hardness of the sponge-like porous body is preferably 90 points or less, more preferably 80 points or less, and particularly preferably 75 points or less when measured with a type A durometer (Kobunshi Keiki Co., Ltd., Asker Rubber Hardness Tester Type A).
[0019] In this embodiment, the hydrophilic performance is improved even in the interior of the sponge-like porous body, but in order to obtain the same performance in the vicinity of the surface and the interior, it is preferable that the thickness of the hydrophilic film on the inner wall of the pores in each region is similar in the vicinity of the surface and the interior. The average thickness of the hydrophilic film on the inner wall of the pores in the thickness direction from the surface part to the back part of the sponge-like porous body, in a region having a depth of 0% to 20% of the thickness of the sponge-like porous body, is defined as D1. The average thickness of the hydrophilic film on the inner wall of the pores in the thickness direction from the surface part to the back part of the sponge-like porous body, in a region (center part) having a depth of 40% to 60% of the thickness of the sponge-like porous body, is defined as D2. In this case, it is preferable that D1 and D2 of the sponge-like porous body of the present invention are both 10 nm or more and 10 μm or less, and 0.7 × D2 ≦ D1 ≦ 1.3 × D2, and it is more preferable that D1 and D2 are both 10 nm or more and 120 nm or less, and satisfy the formula 0.9 × D2 ≦ D1 ≦ 1.1 × D2. Here, the reason why 10 nm or more and 10 μm are desired is that if the film thickness value of the hydrophilic film is smaller than 10 nm, the hydrophilic performance is weak, and conversely, if it is larger than 10 μm, the film stress causes cracking and peeling, impairing the function of the film. The reason why 0.7 × D2 ≦ D1 ≦ 1.3 × D2 is preferable is that the film thickness value is close to obtain the same hydrophilic performance, and although the opening of the pores is narrowed by the film, the film thickness is close to obtain the same size of the opening, and there is no difference in the performance of the sponge-like porous body.
[0020] In the sponge-like porous body of the present invention, the hydrophilic film on the inner wall of the pores of the sponge-like porous body is preferably an oxide film, more preferably an inorganic oxide film. In general, oxide films have high hydrophilicity and have the advantage of having high adhesion to the substrate compared to, for example, organic films. Examples of oxide films include SiO2, Al2O3, TiO2, Ta2O5, HfO2, and RuO2. In the sponge-like porous body of the present invention, the material of the oxide film preferably contains one or a mixture of two or more selected from the group consisting of SiO2, Al2O3, TiO2, Ta2O5, HfO2, and RuO2, and it is particularly preferable that the oxide film contains SiO2 from the viewpoint of hydrophilicity and ease of film formation.
[0021] Furthermore, if the oxide film contains CH groups, they bond with the CH groups contained in the sponge-like porous body, improving the adhesion of the hydrophilic film. Therefore, the oxide film may contain C (carbon). In the sponge-like porous body of the present invention, the C content in the oxide film is preferably 0.5 at% or more and 25 at% or less (0.5 atomic% or more and 25 atomic% or less). This is because if the C content is less than 0.5 at%, it is difficult to detect with an analyzer, and if the C content is more than 25 at%, hydrophilicity is insufficient. The C content in the oxide film can be analyzed by XPS (X-ray photoelectron spectroscopy).
[0022] <Second embodiment> The second embodiment relates to a method for producing a sponge-like porous body. The method for producing a sponge-like porous body of the present invention comprises the steps of: A preparation step of preparing a substrate having holes; a film formation process of forming a hydrophilic film on the inner wall of the pores by ALD (atomic layer deposition); Including, the substrate comprises a foam resin; The substrate contains at least one selected from the group consisting of polyurethane, polyether, and polyethylene. Each step will be described below. The substrate itself is as described above, so a description thereof will be omitted.
[0023] (Preparation process) The method for producing a sponge-like porous body of the present invention includes a preparation step of preparing a substrate having pores. The method for producing the substrate is not particularly limited as long as the desired flexibility and elasticity (hardness) can be obtained, and the following known methods can be used. For example, a hardener and hollow particles (such as resin balloons) are mixed with polyurethane and hardened. Then, a heat treatment is performed to expand the hollow particles to produce a sponge-like porous body. A chemical foaming agent dispersed in polyurethane is decomposed by heat, and bubbles are generated by the generated gas to produce a sponge-like porous body. Alternatively, for example, a W / O type emulsion of polyurethane and water is prepared, and then a hardener is added. After hardening, the water is replaced with air to produce a sponge-like porous body.
[0024] Also, for example, salts are kneaded into polyurethane and a hardener is added. After molding, the salts are dissolved and removed with water or the like to produce a sponge-like porous body. Also, for example, a chemical foaming agent is dispersed in polyurethane, a hardener is added, the chemical foaming agent is decomposed by heating, and bubbles are generated by the generated gas to produce a sponge-like porous body. Also, for example, gas is dissolved in polyurethane by applying pressure, a hardener is added, and then the pressure is reduced to cause foaming by the pressure of the generated gas to produce a sponge-like porous body. Although polyurethane has been given as an example above, these production methods can also be applied to polyether, polyethylene, and other resins. It is preferable that the substrate contains at least one selected from the group consisting of polyurethane, polyether, and polyethylene, and more preferably contains polyurethane. It is preferable that the substrate contains a foam resin. In this way, a sponge-like porous body with flexibility and elasticity can be produced. In the preparation step of the present invention, the substrate may be prepared by the above-mentioned preparation method, or a ready-made substrate may be prepared.
[0025] (Film forming process) The method for producing a sponge-like porous body of the present invention includes a film-forming step of forming a hydrophilic film on the inner wall of the pores by ALD (atomic layer deposition). The method for producing a sponge-like porous body of the present invention includes a film-forming step after the preparation step. As a method for attaching a hydrophilic film with a uniform thickness from the surface to the inside of a sponge-like porous body, for example, ALD (atomic layer deposition) described later can be mentioned. Since ALD supplies the film material as a gas, it is possible to form a film in the range that the gas material can reach. Furthermore, since ALD is a method of stacking atomic layers one by one, it is possible to obtain a uniform film thickness regardless of the shape and location of the substrate. In this way, a sponge-like porous body having hydrophilic properties from the surface to the inside can be produced.
[0026] In the second embodiment, a method for forming a hydrophilic film on the inner walls of the pores of a sponge-like porous body will be described. ALD (atomic layer deposition) can be used to form the hydrophilic film. FIG. 5 shows a schematic diagram of an ALD film forming apparatus. An ALD film forming apparatus 501 includes an exhaust means 503 for evacuating the inside of a chamber, a heater 504 for heating a substrate, and a plurality of gas supply means 507, and can apply a film to a substrate 506 on a substrate holder 505.
[0027] The film formation procedure is as follows. (Step 1) The substrate 506 is placed and evacuated. (Step 2) The substrate 506 is heated to a predetermined temperature by the heater 504. (Step 3) A precursor is supplied through the gas supply means 507. (Step 4) A rare gas such as Ar is introduced through the gas supply means 507 for purging (to remove excess precursor). (Step 5) Reactive gases such as H2O and O2 are supplied through the gas supply means 507 to oxidize the film. (Step 6) A rare gas such as Ar is introduced through the gas supply means 507 for purging. (Step 7) When steps 3 to 6 are counted as one cycle, a film with a thickness of one atomic layer (about 0.1 to 1.0 nm) is formed in one cycle, so the above cycle is repeated until the desired film thickness is achieved. (Step 8) The vacuum chamber 502 is opened to the atmosphere and the substrate 506 is taken out.
[0028] (Through hole formation process) In the method for producing a sponge-like porous body of the present invention, the above-mentioned preparation step preferably includes a through-hole forming step of forming through-holes in the substrate. By doing so, even if the sponge-like porous body has discontinuous pores (pores that are not connected to each other), a sponge-like porous body having hydrophilic properties from the surface to the inside can be produced. Spongy porous bodies can be broadly classified into open-cell type and closed-cell type. In the open-cell type, the pores inside the sponge-like porous body are connected to adjacent pores, while in the closed-cell type, some pores are not connected to adjacent pores and are spatially isolated. When forming a film on these sponge-like porous bodies by ALD, in the open-cell type, the gas material reaches almost all the pores, but in the closed-cell type, it is considered that the gas material does not reach some pores. Therefore, when applying this embodiment to a closed-cell type sponge-like porous body, it is preferable to go through the steps shown in Figures 2(c) and 2(d).
[0029] FIG. 2(a) is a perspective view of a sponge-like porous body (closed-cell type) according to an embodiment of the present invention, and FIG. 2(b) is a schematic diagram of a cross section taken along line A-A' in FIG. 2(a). FIG. 2(c) is a schematic diagram showing a state in the middle of drilling a vertical hole in the sponge-like porous body with a needle, and FIG. 2(d) is a schematic diagram of a cross section taken along line A-A' after drilling a vertical hole in the sponge-like porous body with a needle in FIG. 2(c). A needle 203 is used to drill a vertical hole (through hole) 204 as shown in FIG. 2(c) and 2(d) in a closed-cell type sponge-like porous body 201 as shown in FIG. 2(a) and 2(b). After that, when a hydrophilic film is formed by a method such as ALD, the hydrophilic film can be attached to the pores 202 inside the sponge-like porous body. Furthermore, the vertical hole (through hole) 204 does not necessarily have to be a hole that penetrates from the front surface to the back surface of the sponge-like porous body, but it may be a hole that can connect the pores 202 to the extent that the inside of the sponge-like porous body can have a hydrophilic membrane.
[0030] <Application Examples> Hereinafter, a description will be given of specific application examples in which the sponge-like porous body shown in the first embodiment is used. (Polishing pad) The polishing pad of the present invention preferably has a sponge-like porous body. FIG. 3 illustrates the use of the sponge-like porous body of this embodiment as a polishing pad. FIG. 3(a) is a schematic perspective view of a CMP polishing apparatus 301, and FIG. 3(b) is a side view of FIG. 3(a). Here, CMP stands for Chemical Mechanical Polishing, which is also called chemical mechanical polishing and is a polishing technique that is often used in semiconductor manufacturing processes. In FIGS. 3(a) and 3(b), the object to be polished (workpiece) is a silicon wafer, but is not limited to this. In CMP, a silicon wafer 305, which is a workpiece, is brought into contact with a polishing pad 303 under a load 308.
[0031] Then, while dropping polishing liquid 307 from polishing liquid supply means 306, stage 302 is rotated, and silicon wafer 305 and polishing pad 303 are slid to polish silicon wafer 305 fixed to workpiece holding member 304. Polishing pad 303 may be a single sponge-like porous body of this embodiment or a stack of multiple sponge-like porous bodies. There is no limitation on the thickness of polishing pad 303, but it is about 0.1 to 2.0 mm, and more preferably about 0.4 to 0.8 mm. Furthermore, polishing pad 303 may not be made of the sponge-like porous body of this embodiment alone, and an intermediate layer such as a base material or a cushion layer may be bonded to the opposite side of the polishing surface of the sponge-like porous body.
[0032] The sponge-like porous body of the present invention preferably has a glass polishing rate of 0.70 μm / min or more before an accelerated durability test in the section "(Evaluation of polishing rate and polishing rate stability)" described below and in Table 1. The sponge-like porous body of the present invention preferably has a glass polishing rate of 0.70 μm / min or more after an accelerated durability test. The sponge-like porous body of the present invention preferably has a glass polishing rate of 0.70 μm / min or more when the glass polishing rate after the accelerated durability test is divided by the glass polishing rate before the accelerated durability test, such that the value obtained by dividing the glass polishing rate after the accelerated durability test by the glass polishing rate before the accelerated durability test is 0.70 or more. The sponge-like porous body of the present invention preferably has a wear rate of 0.40 μm / min or less in an accelerated durability test in "(Evaluation of Durability of Polishing Pad)" and Table 1 described below. In this way, the sponge-like porous body can be suitable as a polishing pad. The polishing pad of the application example has a higher polishing effect than a polishing pad not using the sponge-like porous body of the present invention, and has the effect of being able to maintain its performance as a polishing pad even if the polishing pad wears to a certain extent.
[0033] (Liquid absorption pad) Next, a case where the sponge-like porous body of this embodiment is used as a liquid absorbent pad (for example, an ink absorbent pad) will be described. The liquid absorbent pad of the present invention preferably has a sponge-like porous body. FIG. 4 shows a schematic perspective view of a typical inkjet printer. When a printer cover 402 is opened, an inkjet head 403 having ink tanks 404 of multiple colors attached thereto is held by a shaft 405. The inkjet printer 401 draws a desired image on the paper surface by discharging ink onto paper 406 while moving the inkjet head 403 along the shaft 405.
[0034] Inkjet printers often require preliminary ejection. If the printer is not used for a long time, the ink at the tip of the nozzle of the head will inevitably dry and thicken, causing the ejection to become unstable. To prevent this, a certain amount of ink is ejected to refresh the ink before starting drawing. Preliminary ejection ejects unnecessary ink toward the ink absorbing pad. If the ink bounces off the ink absorbing pad or leaks, it will have a negative effect on subsequent drawing, so the ink absorbing pad is required to have high ink retention. The sponge-like porous body of this embodiment has high hydrophilicity and can be used as the ink absorbing pad.
[0035] (Cleaning sponge) Furthermore, the sponge-like porous body of this embodiment can be used as a cleaning sponge. The cleaning sponge of the present invention preferably has a sponge-like porous body. The cleaning sponge referred to here includes sponges for washing dishes, car wash sponges for washing cars, body sponges for washing the human body, and the like, as well as absorbent sponges for wiping water from dishes, cars, and the body. By increasing the hydrophilicity of these cleaning sponges, they have the effect of firmly retaining water and detergent (shampoo) and improving foam retention. In the case of absorbent sponges, the water absorption performance is also increased.
[0036] (Growth sponge) Finally, the sponge-like porous body of this embodiment can be used as a sponge for hydroponic cultivation. The sponge for cultivation of the present invention preferably has a sponge-like porous body. By increasing the hydrophilicity of the sponge for hydroponic cultivation, water and nutrients can be efficiently supplied to plants. EXAMPLES
[0037] The present invention will be specifically described below with reference to examples and comparative examples, but the scope of the present invention is not limited to these examples.
[0038] Example 1 Polyurethane (Tosoh Corporation's Coronate 4370) was used as the resin material, and a hardener (Tosoh Corporation's Nipolan 4479) was selected accordingly, and hollow particles (Matsumoto Microsphere FN-78D, Matsumoto Yushi Seiyaku Co., Ltd.) were mixed in. □200×200mm (200×200mm 2 This compounding agent was placed in a mold for a polishing pad (120°C) and temporarily cured in a 120°C oven for 10 minutes. After primary curing at 120°C for 2 hours, the polishing pad was released from the mold and then secondary cured at 120°C for 8 hours. The thickness of the polishing pad was set to 1.5 mm. A film containing SiO2 (hydrophilic film) was formed on the polishing pad obtained above using the ALD film formation method. 3DMAS was used as the precursor and H2O was used as the reactive gas, forming SiO2 with a thickness of approximately 100 nm.
[0039] Example 2 The same procedure was followed as in Example 1, except that the thickness of the SiO2-containing film was set to about 10 nm.
[0040] Example 3 The same procedure as in Example 1 was followed except that the film containing SiO2 was changed to a film containing Al2O3 (hydrophilic film), TMA was used as the precursor, H2O was used as the reactive gas, and the film thickness was set to about 100 nm.
[0041] Example 4 The same procedure was followed as in Example 3, except that the thickness of the Al2O3-containing film was set to about 10 nm.
[0042] Example 5 The same procedure as in Example 1 was followed except that the C content in the SiO2-containing film was reduced (1.0 at%) and the SiO2-containing film with a low C content was formed using ozone instead of H2O as the reactive gas.
[0043] Example 6 The same procedure as in Example 1 was followed except that the C content in the SiO2-containing film was increased (23.4 at%) and the film containing SiO2 with a high C content was formed by reducing the supply amount of H2O as a reactive gas.
[0044] Comparative Example 1 A simple polyurethane polishing pad was used. The preparation method was the same as in the first half of Example 1, but no SiO2-containing film was formed.
[0045] Comparative Example 2 A polishing pad made by mixing a hydrophilic resin (epoxy resin) with polyurethane was used. Polyurethane (Tosoh Corp., Coronate 4370) and epoxy resin (Mitsubishi Chemical Corp., JER834) were mixed in a ratio of 7:3, and a curing agent (Mitsubishi Chemical Corp., JER Cure FL052) was selected and mixed accordingly, in the same manner as in the first half of Example 1 (except for film formation).
[0046] Comparative Example 3 A polishing pad made by mixing polyurethane with a hydrophilic resin (epoxy resin) was used in the same manner as in Comparative Example 2. The only difference from Comparative Example 2 was that the mixing ratio of polyurethane and epoxy resin was 5:5.
[0047] Comparative Example 4 A hydrophilic resin was sprayed onto the surface of a polyurethane polishing pad. A hydrophilic spray (MAGI-Poly (registered trademark) manufactured by Crystal Optical Co., Ltd.) was applied onto the polishing pad described in Comparative Example 2.
[0048] The evaluation results of each sample are shown in Table 1. Compared to the comparative example, this embodiment achieves both a higher polishing rate and durability (B or higher).
[0049] [Table 1]
[0050] The methods of measurement and evaluation carried out above will be explained. (Hardness measurement) The hardness of the polishing pad was measured using a type A durometer (Asker rubber hardness meter type A, manufactured by Kobunshi Keiki Co., Ltd.). The detailed measurement method was in accordance with the Japanese Industrial Standard JIS K7215.
[0051] (Contact angle measurement) The hydrophilicity of the polishing pad was quantified in terms of contact angle. The contact angle was measured before the polishing pad was worn and after it was worn about 100 μm. The contact angle was measured using a contact angle meter (Kyowa Interface Science Co., Ltd., DropMaster DM300) when 2 μL of pure water was dropped onto the polishing pad. The detailed measurement method was in accordance with the Japanese Industrial Standard JIS R3257.
[0052] (Film thickness measurement (D1, D2 measurement)) The average thicknesses D1 and D2 of the hydrophilic film were measured as follows. First, the sponge-like porous body was cut out so that it would be a square of 10 mm x 10 mm when viewed from above. Next, to evaluate D1, the sponge-like porous body was sliced in the thickness direction from the surface to the back side at 10% of the thickness of the sponge-like porous body to obtain a cross section. Furthermore, to evaluate D2, the sponge-like porous body was sliced in the thickness direction from the surface to the back side at 50% of the thickness of the sponge-like porous body to obtain a cross section. The cross-sectioned sample was measured for the thickness of the hydrophilic film on the inner wall of the pores present in the cross section using a scanning electron microscope (JEOL Ltd., JSM-IT500HR). When the cross section was observed using a scanning electron microscope and 50% or more of the pores in the cross section had a hydrophilic film, the thickness of the hydrophilic film was measured for 20 pores having a hydrophilic film for each cross section, and the average values were taken as D1 and D2. When less than 50% of the pores in the cross section had a hydrophilic film, the values of D1 and D2 were taken as 0.
[0053] (Measurement of C content) To measure the C content (carbon content) of the oxide film in the pores of the polishing pad, a film was formed on a separate Si wafer under the same conditions and to the same thickness, and the film formed on the Si wafer was analyzed with an XPS (X-ray photoelectron spectroscopy) (ULVAC-PHI, Inc., Quantera II) to measure the C content.
[0054] (Evaluation of polishing rate and polishing rate stability) The polishing rate of the polishing pad was evaluated. The glass was polished for a specified time, and the weight of the glass was measured before and after polishing. The polishing rate was calculated from the reduction in the glass weight. The polishing was performed using the device shown in Figure 3 under the following polishing conditions. Workpiece: S-FSL5 (Ohara Co., Ltd.), φ50 Load applied to workpiece: 25kPa Stage rotation speed: 500 rpm Polishing time: 30 minutes Abrasive: Cerium oxide (Mitsui Mining & Smelting Co., Ltd., MIREK (registered trademark) K30-9) The polishing rate was evaluated twice: when the polishing pad was new (before the accelerated durability test) and when the polishing pad was worn down by about 100 μm by the accelerated durability test of the polishing pad described later (after the accelerated durability test). The stability of the polishing rate was evaluated by comparing the two results. The polishing rate was judged as follows: B or higher is preferable. A:1.00μm / min or more B: 0.70μm / min or more, less than 1.00μm / min C: Less than 0.70 μm / min Regarding the stability of the polishing rate, the rate ratio R was defined as follows, and the stability was judged based on the value of R. B or higher is preferable. R = removal rate in worn condition / removal rate in new condition A:R ≧ 0.85 B: 0.70 ≦ R < 0.85 C:R < 0.70
[0055] (Evaluation of durability of polishing pads) The durability of the polishing pad was evaluated by carrying out an accelerated durability test. In the present invention, the accelerated durability test is carried out by using the device shown in Figures 3(a) and 3(b) to use diamond pellets as the workpiece, and creating a situation in which the polishing pad is worn down at an accelerated rate by the diamond pellets. The wear rate is taken as the durability of the polishing pad. The wear conditions are as follows: Workpiece: Diamond pellets, #1200 Load applied to workpiece: 4kPa Stage rotation speed: 110 rpm Wear time: 30 minutes The durability of the polishing pad was evaluated by the above-mentioned method, and the following criteria were set based on the wear rate of the polishing pad. B or higher is preferable. A: Wear rate of polishing pad ≦ 0.20μm / min B: 0.20μm / min < abrasive pad wear rate ≦ 0.40μm / min C: 0.40μm / min < abrasion rate of polishing pad
[0056] Disclosure of the embodiments according to the present invention includes the following configurations and methods. (Configuration 1) A sponge-like porous body having a substrate with pores, A sponge-like porous body, in which the inner walls of the pores have a hydrophilic membrane in a region from a depth of 0% to a depth of 20% or more of the thickness of the sponge-like porous body in the thickness direction from the front surface to the back surface. (Configuration 2) 2. The sponge-like porous body according to claim 1, wherein the hardness of the sponge-like porous body is 90 points or less when evaluated with a type A durometer. (Configuration 3) 3. The sponge-like porous body according to claim 1 or 2, wherein the sponge-like porous body has a thickness of 0.1 mm or more. (Configuration 4) 3. The sponge-like porous body according to claim 1 or 2, wherein the sponge-like porous body has a thickness of 0.5 mm or more. (Configuration 5) 5. The sponge-like porous body according to any one of configurations 1 to 4, wherein the substrate contains a foam resin. (Configuration 6) 6. The sponge-like porous material according to any one of configurations 1 to 5, wherein the base material comprises at least one selected from the group consisting of polyurethane, polyether, and polyethylene. (Configuration 7) 6. The sponge-like porous body according to any one of configurations 1 to 5, wherein the substrate contains polyurethane. (Configuration 8) A sponge-like porous body according to any one of configurations 1 to 7, in which D1 is the average thickness of the hydrophilic film on the inner walls of the pores in a region having a depth of 0% to 20% of the thickness of the sponge-like porous body in the thickness direction from the surface portion to the back portion, and D2 is the average thickness of the hydrophilic film on the inner walls of the pores in a region (center portion) having a depth of 40% to 60% of the thickness of the sponge-like porous body in the thickness direction from the surface portion to the back portion, D1 and D2 satisfy all of the following mathematical formulas: 10nm≦D1≦10μm 10nm≦D2≦10μm 0.7×D2≦D1≦1.3×D2 (Configuration 9) 9. The sponge-like porous material according to any one of configurations 1 to 8, wherein the hydrophilic film is an oxide film. (Configuration 10) 10. The sponge-like porous body according to claim 9, wherein the material of the oxide film contains one or a mixture of two or more selected from the group consisting of SiO2, Al2O3, TiO2, Ta2O5, HfO2, and RuO2. (Configuration 11) 11. The sponge-like porous body according to aspect 9 or 10, wherein the C content in the oxide film is from 0.5 at % to 25 at %. (Configuration 12) 12. A polishing pad comprising the sponge-like porous material according to any one of claims 1 to 11. (Configuration 13) 13. The polishing pad according to claim 12, wherein the polishing rate of glass before an accelerated durability test is 0.70 μm / min or more. (Configuration 14) 14. The polishing pad according to claim 12 or 13, wherein the polishing rate of glass after an accelerated durability test is 0.70 μm / min or more. (Configuration 15) 15. The polishing pad according to any one of configurations 12 to 14, wherein the value obtained by dividing the glass polishing rate after the accelerated durability test by the glass polishing rate before the accelerated durability test is 0.70 or more. (Configuration 16) 16. The polishing pad according to any one of configurations 12 to 15, which has a wear rate of 0.40 μm / min or less in an accelerated durability test. (Configuration 17) 12. A liquid absorbent pad comprising the sponge-like porous material according to any one of claims 1 to 11. (Configuration 18) 12. A cleaning sponge having the sponge-like porous material according to any one of claims 1 to 11. (Configuration 19) 12. A cultivation sponge having the sponge-like porous body according to any one of claims 1 to 11. (Method 1) A preparation step of preparing a substrate having holes; a film formation process of forming a hydrophilic film on the inner wall of the pores by ALD (atomic layer deposition); Including, A method for producing a sponge-like porous body, wherein the base material comprises at least one selected from the group consisting of polyurethane, polyether, and polyethylene. (Method 2) 2. The method for producing a sponge-like porous body according to method 1, wherein the preparation step includes a through-hole forming step of forming through-holes in the substrate. [Explanation of symbols]
[0057] 101 Spongy porous body 102 Vacancy 103 Surface part 201 Sponge-like porous body (closed cell type) 202 Vacancy 203 needles 204 Vertical hole (through hole) 301 CMP polishing equipment 302 Stage 303 Polishing Pad 304 Work holding member 305 Silicon Wafer 306 Polishing liquid supply means 307 Polishing liquid 308 Load 401 Inkjet Printer 402 Printer cover 403 Inkjet head 404 Ink Tank 405 Shaft 406 Paper 501 ALD deposition equipment 502 Vacuum Chamber 503 Exhaust means 504 Heater 505 Substrate Holder 506 Base 507 Gas Supply Means
Claims
1. A sponge-like porous body having a substrate with pores, A sponge-like porous body, in which the inner walls of the pores have a hydrophilic membrane in a region from a depth of 0% to a depth of 20% or more of the thickness of the sponge-like porous body in the thickness direction from the front surface to the back surface.
2. 2. The sponge-like porous body according to claim 1, wherein the hydrophilic film is an oxide film.
3. The material of the oxide film is SiO 2 , Al 2 O 3 , TiO 2 , Ta 2 O 5 , HfO 2 , and RuO 2 3. The sponge-like porous body according to claim 2, which comprises one or a mixture of two or more selected from the group consisting of:
4. 3. The sponge-like porous material according to claim 2, wherein the C content in the oxide film is from 0.5 at % to 25 at %.
5. 2. The sponge-like porous body according to claim 1, wherein the base material comprises at least one material selected from the group consisting of polyurethane, polyether, and polyethylene.
6. The sponge-like porous body according to claim 1 , wherein the substrate comprises polyurethane.
7. The sponge-like porous body of claim 1, wherein D1 is the average thickness of the hydrophilic film on the inner walls of the pores in a region having a depth of 0% or more and 20% or less of the thickness of the sponge-like porous body in the thickness direction from the surface portion to the back portion, and D2 is the average thickness of the hydrophilic film on the inner walls of the pores in a region (center portion) having a depth of 40% or more and 60% or less of the thickness of the sponge-like porous body in the thickness direction from the surface portion to the back portion, D1 and D2 satisfy all of the following mathematical formulas. 10 nm≦D1≦10 μm 10 nm≦D2≦10 μm 0.7 x D2 ≤ D1 ≤ 1.3 x D2
8. 2. The sponge-like porous body according to claim 1, wherein the hardness of the sponge-like porous body is 90 points or less as evaluated by a type A durometer.
9. 2. The sponge-like porous body according to claim 1, wherein the thickness of the sponge-like porous body is 0.1 mm or more.
10. 2. The sponge-like porous body according to claim 1, wherein the thickness of the sponge-like porous body is 0.5 mm or more.
11. The sponge-like porous body according to claim 1 , wherein the substrate comprises a foam resin.
12. A polishing pad comprising the sponge-like porous body according to any one of claims 1 to 11.
13. 13. The polishing pad according to claim 12, wherein the polishing rate of glass before an accelerated durability test is 0.70 μm / min or more.
14. 13. The polishing pad according to claim 12, which has a glass polishing rate of 0.70 μm / min or more after an accelerated durability test.
15. 13. The polishing pad according to claim 12, wherein a value obtained by dividing the glass polishing rate after the accelerated durability test by the glass polishing rate before the accelerated durability test is 0.70 or more.
16. 13. The polishing pad according to claim 12, which has a wear rate of 0.40 μm / min or less in an accelerated durability test.
17. A liquid absorbent pad comprising the sponge-like porous body according to any one of claims 1 to 11.
18. A cleaning sponge comprising the sponge-like porous body according to any one of claims 1 to 11.
19. A cultivation sponge having the sponge-like porous body according to any one of claims 1 to 11.
20. A preparation step of preparing a substrate having holes; a film formation process of forming a hydrophilic film on the inner wall of the hole by ALD (atomic layer deposition); Including, A method for producing a sponge-like porous body, wherein the base material comprises at least one material selected from the group consisting of polyurethane, polyether, and polyethylene.
21. The method for producing a sponge-like porous body according to claim 20 , wherein the preparation step includes a through-hole forming step of forming through-holes in the substrate.
Citation Information
Patent Citations
Polishing pad
JP2015120220A